2(3+-4x)-5(2x+3)=x+-

Simple and best practice solution for 2(3+-4x)-5(2x+3)=x+- equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(3+-4x)-5(2x+3)=x+- equation:



2(3+-4x)-5(2x+3)=x+-
We move all terms to the left:
2(3+-4x)-5(2x+3)-(x+-)=0
We add all the numbers together, and all the variables
2(-4x)-5(2x+3)-(+x)=0
We multiply parentheses
-8x-10x-(+x)-15=0
We get rid of parentheses
-8x-10x-x-15=0
We add all the numbers together, and all the variables
-19x-15=0
We move all terms containing x to the left, all other terms to the right
-19x=15
x=15/-19
x=-15/19

See similar equations:

| 94+X=3x | | x.3=180 | | 10(x)/(3)=90 | | 15c=c+42 | | 9/x=36/16 | | 180=x.3 | | 16s-38=11s-13 | | n-11=2n+4 | | 11s-13=16s-38 | | (x-15)/5=-2 | | a+2=5-4a | | 610=x25 | | (x-15)÷5=-2 | | 4(x-1)-5x=-2 | | 7y+25=2y-13 | | -7.3=u/8+5.5 | | -1.87-x=2 | | w(w-6)+w(w-6)=1 | | -2.3+y/7=-19,8 | | 52-5x=2x-15 | | –7.5p+2.66=1.74−7.6p | | 5x-52=2x-15 | | 22-2y=8 | | y(4)+13y″+36y=0 | | 4x+38=2x-28 | | 4x+38=3x-28 | | 6w+20=20 | | 7z+8=-4z-10+2z | | -1/2(4x+8)^2-16=6 | | 4w+4=6w-8 | | 9s-3-2s=10s+9 | | -10q-10-3q=-3q+10 |

Equations solver categories